Competition in lexical processing of Italian noun/verb homographs. Issue 5 (3rd July 2016) - Postiglione, Francesca; Laudanna, Alessandro
ABSTRACT: The study investigates the lexical representation of Italian noun/verb homographs, introducing a factor which has been analysed in production studies: the specific-word frequency (SWF). The SWF parameter allows to understand whether the grammatical class information is specified within the lexical knowledge or it is selected during post-lexical stages. We ran six lexical decision tasks employing the priming paradigm and a grammatical decision task to investigate the lexical representation of noun/verb homographs. In addition, we sought to determine the role played by the frequency of representations and the temporal activation of the grammatical class information. Our findings support the claim that these forms have independent representations for each syntactic role they can play. We interpreted these findings in the light of what we call the "Nominal Dominance" effect, which affects the lexical access of noun/verb homographs. We also discuss the relation between nominal dominance and lexical frequency.